ANALISIS ETIKA PESERTA DIDIK KAJIAN TAFSIR AL MISBAH KARYA QURAISH SHIHAB - Darwis, Muhajir; Supriadi, Agus; Rofiki, Sahari (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2024)
Success in the pursuit of knowledge is determined by the ethics possessed by students. Therefore, students are required to have good ethics to get this success. If students do not have good ethics, efforts to determine knowledge will be in vain. Improving student ethics in studying is the same as improving existing education. This is because ethics in studying cannot be separated from education. This study uses library research methods with the aim of collecting data or scientific papers related to the research title. This study aims to examine the verses that explain the ethics of students in studying. These verses are studied using the interpretation of Al-Misbah by Qurais Shihab which is related to education. From this study resulted in an explanation of the ethics that must be possessed by students. These ethics include: 1). Be patient; 2). obey the teacher; 3). not interrupting the teacher's explanation; 4). ask people who know about the science being studied; 5). gentle when communicating with the teacher. Through this research it is hoped that it will become a reference source for literacy for readers, especially students, to be able to have ethics when studying.